Influence of sonication and in vitro evaluation of nifedipine self-nanoemulsifying drug delivery system - Ahmad M Eid; Nagib A Elmarzugi; Nidal A Jaradat (Universidade de São Paulo, 2019)
In order to develop a self-nanoemulsifying system, three components, olive oil, Tween 80, and Capmul, were used to construct a ternary phase diagram that helped to find the optimum formulation, which was loaded with nifedipine. The effect of sonication on drug loading was also evaluated. After that, measurement of the droplet size, size distribution, zeta potential, and scanning electron microscopy were conducted for evaluation and characterisation of the formulations. The phase diagram of four formulations showed nanosizes below 200 nm; however, only one was selected to be loaded with nifedipine. The selected formulation had the lowest droplet size of 98 nm and size distribution 0.192, and was composed of 48% Tween 80, 32% Capmul, and 20% olive oil. The nifedipine self-nanoemulsifying drug delivery system (SNEDDS) showed a significant change in the particle size (97 nm) and size distribution (0.257) after sonication. Its zeta potential was -32.3 mV indicating good stability. The SEM photographs of nifedipine showed particles with spherical shape and smooth surface. Finally, a self-nanoemulsifying formulation containing nifedipine, loaded in olive oil, was successfully prepared by mixing the oil with various types of surfactants and co-surfactants. A significant nifedipine self-nanoemulsifying system was developed and significantly improved accordingly.